2012
DOI: 10.5480/1536-5026-33.4.251
|View full text |Cite
|
Sign up to set email alerts
|

FOCUSonRETENTION:Identifying Barriers to Nurse Faculty Satisfaction

Abstract: There has been a great deal of attention focused upon the professional and faculty nursing shortage. Retirement rates of seasoned nurse faculty, fewer nurses pursuing academic roles as nursing faculty, and insufficient numbers of nurses in doctoral programs hinder the ability to educate willing students to become professional nurses. The aim of this descriptive, quantitative study in the New England region was to determine barriers to job satisfaction as reported by nurse faculty. A 32-item survey was used wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 6 publications
2
46
0
Order By: Relevance
“…According to a nursing faculty census, more than 50% of junior faculty had not met criteria for scholarship that supports promotion and tenure, including publication, grant funding, and national presentations (NLN, 2002). The assumption of multiple roles; dealing with competing priorities; balancing the tripartite mission of research, education, and service (Banks, 2012; Garand et al, 2010); and the lack of mentoring (Bittner & O’Connor, 2012; Nies & Troutman-Jordan, 2012; Specht, 2013) often serve as barriers to junior nursing faculty success as they enter academia.…”
Section: Discussionmentioning
confidence: 99%
“…According to a nursing faculty census, more than 50% of junior faculty had not met criteria for scholarship that supports promotion and tenure, including publication, grant funding, and national presentations (NLN, 2002). The assumption of multiple roles; dealing with competing priorities; balancing the tripartite mission of research, education, and service (Banks, 2012; Garand et al, 2010); and the lack of mentoring (Bittner & O’Connor, 2012; Nies & Troutman-Jordan, 2012; Specht, 2013) often serve as barriers to junior nursing faculty success as they enter academia.…”
Section: Discussionmentioning
confidence: 99%
“…4 Perceptions of workload are an integral part of job satisfaction for nurse faculty retention. 16 There is a need for development and evaluation of workload models that include all aspects of faculty work in the current educational environment and that are also informed by universities promotion and tenure guidelines and departmental resources. 4,16 Development of the Lead Faculty Workload Model…”
Section: Nurse Faculty Shortage and Increased Enrollmentmentioning
confidence: 99%
“…Several studies identified barriers to job satisfaction and examined factors responsible for the retention of nursing academics (Bittner & O'Connor, 2012;Tourangeau et al, 2013). In relation to the barriers to job satisfaction, findings (Bittner & O'Connor, 2012;Tourangeau et al, 2013) indicated that 57% of the participants (n = 226) felt that a sense of accomplishment, coupled with autonomy in the role (50%), having healthy relationships with colleagues (49.3%) and feeling safe at work (38.5%), did contribute to greater job satisfaction (Bittner & O'Connor, 2012) including quality mentoring (Gwyn, 2011).…”
Section: Re Sultsmentioning
confidence: 99%
“…Several studies identified barriers to job satisfaction and examined factors responsible for the retention of nursing academics (Bittner & O'Connor, 2012;Tourangeau et al, 2013). In relation to the barriers to job satisfaction, findings (Bittner & O'Connor, 2012;Tourangeau et al, 2013) indicated that 57% of the participants (n = 226) felt that a sense of accomplishment, coupled with autonomy in the role (50%), having healthy relationships with colleagues (49.3%) and feeling safe at work (38.5%), did contribute to greater job satisfaction (Bittner & O'Connor, 2012) including quality mentoring (Gwyn, 2011). Some of the factors identified that contributed to greater job satisfaction in nursing academia included the need to have a better work-life balance (Roughton, 2013), secured tenureship (Smeltzer et al, 2015), have high levels of work-related empowerment (Sarmiento et al, 2004), greater engagement in assessing faculty quality of education and supporting collegial relationships (Tourangeau et al, 2013), have better teaching support and realistic workloads (Yedidia et al, 2014), more rewarding remuneration in salary (Westphal et al, 2016) and elimination of social bullying (Wieland & Beitz, 2015).…”
Section: Re Sultsmentioning
confidence: 99%